AI AS TEACHING PARTNER: EXAMINING EFL EDUCATORS' PRACTICES IN ONLINE READING COMPREHENSION - Aldha Williyan; Ema Wilianti Dewi; Kautsar Kautsar (IAIN Syekh Nurjati Cirebon, 2025)
This study examines how EFL teachers incorporate Artificial Intelligence (AI) into teaching reading comprehension in online environments, with a focus on its role in lesson planning, delivery, and evaluation. The research aims to understand the diverse ways educators adopt AI tools in their practices. Using a qualitative approach, involving interviews and classroom observations, the study captures teachers' experiences with AI integration. Findings reveal that AI enhances the personalization of reading materials, enables real-time feedback during lessons, and streamlines the grading process. However, the study also highlights differing attitudes toward AI, as some teachers prefer traditional methods, citing concerns about losing pedagogical control and the limitations of AI technology. The study concludes that, while AI holds significant potential for improving instructional practices, there is a clear need for professional development programs to help teachers effectively balance AI use with traditional pedagogical methods. Future research should investigate the long-term effects of AI on student learning outcomes, examine AI's influence on teacher-student interactions, and evaluate the role of professional development in supporting AI adoption in education.